PENERAPAN AQUAPONIK DAN PENGEMBANGAN BUDIDAYA IKAN LELE PADA UNIT USAHA PONDOK PESANTREN KOTA MALANG - Abdul Halim; Suslam Pratamaningtyas (Jurnal Layanan Masyarakat (Journal of Public Services), 2020)
Tarbiyatul Iman Islamic Boarding School (PPTI) located on Jalan Perum Srigading Dalam Kav 11 Malang has a catfish breeding business under the name "Catfish PPTI". The catfish farmers group is a partner in the community partnership program (PKM). The partner group is hoping for good management of fish culture production. The appropriate technology is technology in cultivating fish with a "Bionic" system that combines organic fish farming with organic vegetable plants in limited lands, with the intention of feeding and place efficiency and operational costs. The implementation of PKM in Tarbiyatul Iman Islamic Boarding School (PPTI) begins with coordination with the management. PPTI already has 2 catfish ponds which have been managed as they are as learning media for students. With the existence of this PKM, the number of ponds owned by PPTI has become 7 ponds, plus the installation of aquaponics with a pot system and pipes. There are two aquaponic system models implemented in PPTI, namely the first model where vegetables are grown in pots filled with planting media consisting of gravel / zeolite and husks. Pond water is channeled into plant pots which are arranged on top of a pool and flows out into the pond. While the second model is pond water flowed into PVC pipes, where the pipes are perforated and filled with plants that have been planted in a net pot and the water will be re-inserted into the fish pond. AbstrakPondok Pesantren Tarbiyatul Iman (PPTI) yang berlokasi di Jalan Perum Srigading Dalam Kav 11 Malang mempunyai unit usaha budidya ikan lele dengan nama “Lele PPTI”. Kelompok pembudidaya ikan lele ini merupakan mitra program kemitraan masyarakat (PKM). Kelompok mitra mengharapkan manajemen produksi budidaya ikan yang baik. Teknologi tepat guna tersebut adalah teknologi membudidayakan ikan dengan sistem” Bionic” yaitu menggabungkan budidaya ikan secara organik dengan tanaman sayur organik di lahan terbatas, dengan maksud efisiensi pakan, tempat, serta biaya operasional. Pelaksanaan PKM di Pondok Pesantren Tarbiyatul Iman (PPTI) diawali koordinasi dengan para pengurus. PPTI sudah memiliki 2 buah kolam ikan lele yang selama ini dikelola apa adanya sebagai media pembelajaran bagi santri. Dengan adanya PKM ini, jumlah kolam yang dimiliki PPTI menjadi 7 buah kolam, ditambah dengan instalasi aquaponik sistem pot dan pipa. Ada dua model system aquaponik yang diterapkan, yaitu pertama dimana sayuran ditanam dalam pot yang diisi media tanam yang terdiri dari batu kerikil/zeolite dan sekam. Air kolam dialirkan ke pot-pot tanaman yang disusun di atas kolam ikan dan mengalir keluar kembali masuk ke kolam. Model kedua adalah air kolam dialirkan ke dalam pipa-pipa PVC, pipa-pipa tersebut dilubangi dan diisi tanaman yang telah disemaikan pada net pot dan air akan kembali dimasukkan ke dalam kolam ikan.